2024
DOI: 10.3389/fpubh.2023.1349174
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of severity levels of anemia among women of reproductive age in sub-Saharan Africa: a multilevel ordinal logistic regression analysis

Lire Lemma Tirore,
Abriham Shiferaw Areba,
Aklilu Habte
et al.

Abstract: BackgroundSub-Saharan Africa is the most anemia-prone region, with several of the sub-region’s countries having a substantial prevalence of the anemia among women of reproductive age. Nonetheless, no adequate study has been conducted to illustrate severity levels and associated factors of anemia among women of reproductive age. Therefore, this study presents the most recent estimates on the prevalence and severity levels of anemia and its associated factors among women of reproductive age in 21 Sub-Saharan Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…14 A study conducted in sub Saharan African countries had reported mild anemia 23.45%, moderate 17.05% and severe anemia as 1.24%. 20 All these results were comparable to our study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…14 A study conducted in sub Saharan African countries had reported mild anemia 23.45%, moderate 17.05% and severe anemia as 1.24%. 20 All these results were comparable to our study.…”
Section: Resultssupporting
confidence: 91%
“…Another study done in America in 2015 showed that the frequency of anemia was with minor category with frequency from 7.6% to 18.7% in some areas while moderate ranging from 21.4% to 38.3% and anemia was measured as a severe community health issue in different countries. 16 In our study the age range was between 20…”
Section: Resultsmentioning
confidence: 79%